Analysis of Physical, Chemical, and Biological Peat Water Quality on The Degree of Health of Gampong Sumber Bakti Communities - Berutu, Nova Sarwedi; Kiswanto, Kiswanto; Rimonda, Rubi; Wintah, Wintah (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2024)
Peat water is the source of water used by the people of Gampong Sumber Bakti. This study aimed to analyze the quality of peat water with parameters ofß color, taste and smell, turbidity, pH, TDS, iron (fe), manganese, E. coli, temperature, and complaints about public health status. Sampling was done by purposive random sampling of as many as 42 respondents in Gampong Sumber Bakti. The sampling of peat water was carried out by random sampling. The data is obtained from the experimental results of the Tirta Meulaboh Regional Drinking Water Company Laboratory. At the same time, data on public health degree complaints through surveys and interviews using questionnaire media. The results of the study stated that the examination of physical and chemical parameters exceeded the threshold based on Permenkes No. 32 of 2017, color 120 TCU, taste and smell, temperature 28.5 oC, turbidity 34 NTU, Mn 0.69 Mg/l, Fe 1.6 Mg/ l, pH 6.84 Mg/l, TDS 1200 Mg/l and no biological E.coli was detected. Meanwhile, public health complaints were itching at 21.4%, diarrhea at 7.1%, scaly skin at 23.8%, porous teeth at 4.8%, stickiness at 33.3%, and other complaints at 9.5%. The suggestions that researchers can give are providing simple filtration, building clean water facilities, improving